Perubahan Sosial-Budaya dalam Lagu Daerah Bima Karya Gun Malingi: Socio-Cultural Change in Bima Regional Songs by Gun Malingi - Nurul Istiqomah; A. Haris; Evelin Giovani; Rosalia Floriani; Sijabat, Survey; Arin Mantara Anggawirya (Information Technology and Science(ITScience), 2025)
Regional songs are authentic sources that represent the socio-cultural life of the communities in which they emerge. Therefore, research is needed to examine how the socio-cultural conditions of the Bima people are represented in the regional songs Kambali Mbojo Mantoi and Tio Kalao by Gun Malingi. This study aims to reveal the socio-cultural changes reflected in these two songs as well as the didactic values embedded within them. The research employs a literary sociology approach supported by social change theory. A descriptive qualitative method is applied to analyze the song lyrics, focusing on the socio-cultural changes and didactic values they contain. The findings show that: (1) the songs represent socio-cultural changes through the diminishing presence of several Bima traditions, such as pako fare, doa dana, rawi rasa, kareku kandei, and rimpu mpida; (2) the songs also depict shifts in the relationship between humans and nature; and (3) the researcher identifies didactic values in the form of Bima local wisdom ngaha aina ngoho which serves to reinforce educational values. These changes indicate a regression within the Bima community, marked by the fading of socio-cultural values and environmental degradation. Ultimately, these Bima regional songs play a vital role in preserving and sustaining Bima cultural identity and traditions, while fostering collective awareness of the importance of safeguarding cultural values, traditions, and the natural environment amid modern social change.